2003
DOI: 10.1103/physrevlett.90.256101
|View full text |Cite
|
Sign up to set email alerts
|

Seeing the Atomic Orbital: First-Principles Study of the Effect of Tip Termination on Atomic Force Microscopy

Abstract: We perform extensive first-principles calculations to simulate the topographical atomic-force-microscope image of an adatom on the Si(111)-(7 x 7) surface, demonstrating the feasibility of imaging not only the atoms but also the atomic orbitals. Our comparative study of tip terminations shows that two subatomic features can appear for a single adatom when it is imaged by a Si(001)-type tip having two dangling bonds on its apex, while only one feature would appear if it were imaged by a Si(111)-type tip having … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 21 publications
2
41
0
Order By: Relevance
“…10 Subsequently, it was shown that these features could be reproduced with the lobes aligned in directions not perpendicular to the scan direction, 11 and theoretical calculations suggested that the double lobe features might indeed be observable. 12 However, it should be noted that due to the computational constraints of the time these simulations involved a number of simplifications, including the use of very small tip-clusters and the fixing of the tips atoms during the calculation of the tip-sample forces. Later, more sophisticated calculations 13 performed without these limitations suggested that the original model put forward to explain the double lobe features was perhaps over-simplified, and, even if unphysically constrained, did not produce the "double lobe" features observed experimentally or observed in earlier simulations.…”
Section: Introductionmentioning
confidence: 99%
“…10 Subsequently, it was shown that these features could be reproduced with the lobes aligned in directions not perpendicular to the scan direction, 11 and theoretical calculations suggested that the double lobe features might indeed be observable. 12 However, it should be noted that due to the computational constraints of the time these simulations involved a number of simplifications, including the use of very small tip-clusters and the fixing of the tips atoms during the calculation of the tip-sample forces. Later, more sophisticated calculations 13 performed without these limitations suggested that the original model put forward to explain the double lobe features was perhaps over-simplified, and, even if unphysically constrained, did not produce the "double lobe" features observed experimentally or observed in earlier simulations.…”
Section: Introductionmentioning
confidence: 99%
“…S3). The possibility of detecting subatomic contrast has been discussed previously based on DFT calculations by Huang et al (27) Figure 1K is an AFM image of an Fe atom on an Fe island. Its threefold symmetry is explained by the contribution of 3d states, as shown in Fig.…”
mentioning
confidence: 96%
“…Now, FM-AFM is a routine method (34,12) for imaging conductive and insulating surfaces with atomic resolution that even enables the direct measurement of chemical-bonding forces (35) by using deconvolution techniques (36). An optimized sensing technology has led to the observation of subatomic features within a single atom spaced by 220 pm (37), related to the orbital structure of a Si atom (38). The rest atoms on Si (111)-(7ϫ7) were imaged by lowtemperature AFM (39) and small-amplitude techniques (40), demonstrating a lateral resolution of 384 pm.…”
mentioning
confidence: 99%